How could Chinese companies transfer their role of traditional manufacturer in international value chain to knowledge-based economy? - Ma, Xiaoxiao (2014)
This dissertation is expected to explore the industrial situation faced by Chinese manufacturers and provide managers in Chinese manufacturing industry a strategic recommendation to help them improve their profitability. The research in this dissertation mainly investigated the opinions of Chinese managers in manufacturing industry on the knowledge-based strategy and how these Chinese manufacturers solve their business problems like profit reduction. Some recommendations are claimed at the end of this dissertation.